(3QSGdI GdEjVGM HYLeI GdEaUGMs - (3CHh eMeO YHO Gddg Hf MeRI Hf SdjeGf Hf MeRI GdMSfj Gdjefj,J (B614 (3g` s
(3ChdgG (B:s
(3GdMeO ddg aGWQ GdSehGJ hGdCQV , GdYRjR GdMcje , GdeaGVd Hjf YHGOg YOdkG hJcdjakG s
(3BNQgG (B:s
(3EdG Cf jQLY Yf cKH , hGddg GdeJSYGf hGdeSJLGO hSjYde GdcGaQ def YbHi GdOGQ hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B21s
(3HgG fXGe GdJYbjHIs
(3LhGH eWGYf GdbGVi eMeO Hf fThGfs
(3ef GdCFeIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds